The Mutual Impact of Global Strategy and Organizational Learning: Current Themes and Future Directions. (May 2015) - Hotho, Jasper J.; Lyles, Marjorie A.; Easterby‐Smith, Mark
Abstract : Despite the interest in issues of knowing and learning in the global strategy field, there has been limited mutual engagement and interaction between the fields of global strategy and organizational learning. The purpose of our article is to reflect on and articulate how the mutual exchange of ideas between these fields can be encouraged. To this end, we first conduct a review of the intersection of the fields of global strategy and organizational learning. We then present two recommendations regarding how the interaction between the two fields can be enhanced. Our first recommendation is for global strategy research to adopt a broader notion of organizational learning. Our second recommendation is for global strategy research to capitalize on its attention to context in order to inform and enhance organizational learning theory. We discuss the use of context in a number of common research designs and highlight how the scope for theoretical contributions back to organizational learning varies with the research design that is adopted.